Changes in human tear metabolome following topical 0.05% cyclosporine A on primary Sjögren’s syndrome - Li, Yingsi; Huang, Meiting; Xie, Luoying; Yan, Xiaoming; Song, Wenjing (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to investigate changes in the tear metabolome and the therapeutic impact of 0.05% cyclosporine A (CsA) eye drops in patients with dry eye disease (DED) linked to primary Sjögren’s syndrome (pSS).MethodsFifteen patients with pSS-related DED were treated with topical 0.05% CsA for 3 months. Ocular examinations were performed, and tear samples were collected at baseline (T0) and 3 months post-treatment (T1). Differentially expressed metabolites were detected and correlated with clinical parameters.ResultsTopical 0.05% CsA treatment significantly improved the Ocular Surface Disease Index score, lid margin vascularity, conjunctival staining, tear breakup time (TBUT), and lid wiper epitheliopathy (LWE) in DED patients (all p < 0.05). A total of 402 metabolites were identified in pSS patients’ tear fluid, with 64 showing differential expression. Pathway analysis identified significant enrichment in the biosynthesis pathways of phenylalanine, tyrosine, and tryptophan. Additionally, certain metabolites (e.g., lipids and anti-inflammatory molecules) correlated positively or negatively with clinical parameters such as TBUT, LWE, and conjunctival staining.ConclusionThis study underscores significant alterations in tear metabolites at the ocular surface in pSS patients receiving 0.05% topical CsA, offering important insights for managing pSS-related DED clinically.